Association of the Usability of Electronic Health Records With Cognitive Workload and Performance Levels Among Physicians - Mazur, Lukasz M. (JAMA Netw Open, 2019)
IMPORTANCE: Current electronic health record (EHR) user interfaces are suboptimally designed and may be associated with excess cognitive workload and poor performance. OBJECTIVE: To assess the association between the usability of an EHR system for the management of abnormal test results and physicians’ cognitive workload and performance levels. DESIGN, SETTING, AND PARTICIPANTS: This quality improvement study was conducted in a simulated EHR environment. From April 1, 2016, to December 23, 2016, residents and fellows from a large academic institution were enrolled and allocated to use either a baseline EHR (n = 20) or an enhanced EHR (n = 18). Data analyses were conducted from January 9, 2017, to March 30, 2018. INTERVENTIONS: The EHR with enhanced usability segregated in a dedicated folder previously identified critical test results for patients who did not appear for a scheduled follow-up evaluation and provided policy-based decision support instructions for next steps. The baseline EHR displayed all patients with abnormal or critical test results in a general folder and provided no decision support instructions for next steps. MAIN OUTCOMES AND MEASURES: Cognitive workload was quantified subjectively using NASA–Task Load Index and physiologically using blink rates. Performance was quantified according to the percentage of appropriately managed abnormal test results. RESULTS: Of the 38 participants, 25 (66%) were female. The 20 participants allocated to the baseline EHR compared with the 18 allocated to the enhanced EHR demonstrated statistically significantly higher cognitive workload as quantified by blink rate (mean [SD] blinks per minute, 16 [9] vs 24 [7]; blink rate, –8 [95% CI, –13 to –2]; P = .01). The baseline group showed statistically significantly poorer performance compared with the enhanced group who appropriately managed 16% more abnormal test results (mean [SD] performance, 68% [19%] vs 98% [18%]; performance rate, –30% [95% CI, –40% to –20%]; P < .001). CONCLUSIONS AND RELEVANCE: Relatively basic usability enhancements to the EHR system appear to be associated with better physician cognitive workload and performance; this finding suggests that next-generation systems should strip away non–value-added EHR interactions, which may help physicians eliminate the need to develop their own suboptimal workflows.